2007
DOI: 10.1002/cbdv.200790192
|View full text |Cite
|
Sign up to set email alerts
|

Re‐Mapping Robert Rosen's (M,R)‐Systems

Abstract: The central concern of this paper is to re-evaluate Rosen's replicating (M,R)-systems, presented in his book 'Life Itself ', where M and R signify metabolism and repair, respectively. We look anew at Rosen's model of an organism in the light of extensive research into natural hierarchical systems, and the paper presents conclusions drawn from a comparison between Rosen's relational model and that of a birational complementary natural hierarchy. We accept that Rosen's relational model provides a useful stepping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…Closure to efficient cause, illustrated in Rosen (1991), shown (a) in the unsymmetrical way used by Rosen, (b) in the more symmetrical way suggested by Cottam et al (2007), and (c) in a way suggested by Goudsmit (2007) in which the representation of efficient causes resembles normal practice in chemistry, with catalysts shown as acting on reactions rather than on substrates. (d) In all three variants full arrows represent material causation, or chemical transformation, whereas broken arrows show efficient causation, or catalysis.…”
Section: Closure To Efficient Causementioning
confidence: 99%
See 1 more Smart Citation
“…Closure to efficient cause, illustrated in Rosen (1991), shown (a) in the unsymmetrical way used by Rosen, (b) in the more symmetrical way suggested by Cottam et al (2007), and (c) in a way suggested by Goudsmit (2007) in which the representation of efficient causes resembles normal practice in chemistry, with catalysts shown as acting on reactions rather than on substrates. (d) In all three variants full arrows represent material causation, or chemical transformation, whereas broken arrows show efficient causation, or catalysis.…”
Section: Closure To Efficient Causementioning
confidence: 99%
“…1a. Cottam et al (2007), have argued that the underlying logic is symmetrical and can be better illustrated with a symmetrical figureof-eight layout, as in Fig. 1b.…”
Section: Closure To Efficient Causementioning
confidence: 99%
“…We have indicated elsewhere that hierarchy is a basic prerequisite for life (Cottam, Ranson and Vounckx 2005), and that a living entity is its hyperscalar representation (Cottam, Ranson and Vounckx 2006a). Close examination of Rosen's (1991) model of an organism reveals that it is the monoscalar contraction of a naturally hyperscalar entity (Cottam, Ranson, and Vounckx 2006b;Cottam, Ranson and Vounckx 2007a). Terrence Deacon (1997) has suggested that being alive is what it feels like to be evolution happening.…”
Section: Sapience and Lifementioning
confidence: 99%
“…On the other hand, there is the metrical biology that encompasses the reducionistic approach of modern biology and biotechnology. This approach allows one to know the biological structures involved on a phenomenon in details, but it rely mostly on the assumption that structure imply function [2]. In other words, the knowledge of all smalls structures involved in a phenomenon implies the knowledge of all its function and leads ultimately to the understanding, description, and prediction of the subject matter.…”
Section: Introductionmentioning
confidence: 99%
“…In order to answer and reconcile these questions it is necessary to build a general theory that turns it possible to approach biology conceptually and experimentally. Modern biology have shown that it has no discourse to offer this theory, since biological phenomena are resilient to final reduction in terms of Cartesian method [2]. This fact of resilience is due to the nature of these phenomena and how we understand them.…”
Section: Introductionmentioning
confidence: 99%